Netflix: Comparison of the Impact of Social Media Content on Social Media Engagement Behaviour Between Followers of the Series and the Platform - Rumaldo-Calderón, Camila (2024)
Brands have identified an opportunity to develop Social Media Engagement Behaviour (SMEB) in their users through Social Media Content (SMC) tools within social networks, such as Facebook. However, they fail to understand whether users are really engaged with them or with their products, especially if both scenarios have their own identities in social networks and different followers. The present research compares the SMEB generated in both scenarios, contrasting the followers of Netflix on Facebook and the official pages of its series. Data were collected by applying two online surveys to 284 users. Subsequently, they were analysed through the PLS-SEM multivariate analysis method based on a second-order construct. The study concludes that the SMEB found in users who follow Netflix’s fan page as a brand is higher than that of its series on Facebook, thus revealing a predominance of preference, in terms of content on social networks, for the brand over the product.